Registration and outcome reporting bias in randomised controlled trials of distal radius fracture treatment: a systematic review - Lee, Sheila; Khan, Tanvir; Grindlay, Douglas; Karantana, Alexia (Lippincott, Williams & Wilkins:, 2018)
Background: The aim was to systematically evaluate the completeness of trial registration and the extent of outcome-reporting bias in modern randomised controlled trials (RCTs) of distal radius fracture treatment. This is the first study to investigate this in the setting of a single, common, well-researched orthopaedic injury and across all journal publications. Methods: Utilizing four databases (PubMed, Cochrane, Embase and PEDro), this systematic review identified all RCTs of distal radius fracture treatment published from January 2010 to December 2015. We independently determined the registration status of these trials in a public trial registry and compared characteristics of registered and non-registered trials. We assessed quality and consistency of primary outcome measure (POM) reporting between registration and final published reports. Results: Ninety studies fulfilled the inclusion criteria. Of the 90 RCTs, only 31% (28/90) were registered; 3% (3/90) were "appropriately registered" i.e. registered prospectively, identifying and fully describing the POM. Registered trials had larger sample sizes, were more likely to be multi-centre, to report funding sources and be published in higher impact factor journals. Of the 16 (18%, 16/90) registered RCTs which named a POM, seven (7/16, 44%) stated a different or additional POMs in the final publication, whereas 13 (13/16, 81%) had discrepancies in the time-point reported for the POM. Conclusion: Prospective trial registration in a public registry has been deemed a condition for publication by the International Committee of Medical Journal Editors (ICMJE) since 2005, in an attempt to address publication and outcome-reporting bias. This study demonstrates poor registration rates and inconsistencies in the reporting of primary outcomes measures of recent trials of distal radius fracture treatment, one of the most common and most investigated injuries in orthopaedic practice. Clinical relevance: This problem is important to highlight and address with the cooperation of researchers, reviewers, journal editors and the scientific community as a whole. Increasing the transparency and consistency of reporting will help drive up the quality of distal radius fracture research, which increasingly impacts on patient care through evidence-based guidelines.